Experimental study of the influence of ply orientation on DCB mode-I delamination behavior by using multidirectional fully isotropic carbon/epoxy laminates - Mohamed Rehan, Muhammad Saifuddin; Rousseau, Jerome; Fontaine, Stephanie; Gong, Xiaojing (Elsevier BV, 2017)
The influence of ply orientation on the resistance to mode I delamination of multidirectional composite laminates can be assessed by Double Cantilever Beam (DCB) tests. However, one difficulty is to uncouple the global and local effects due to the stacking sequence, which is necessary for a conclusive analysis. In the present work six multidirectional DCB specimens were designed so as to obtain an uncoupled fully isotropic elastic behavior, with the same properties for the entire laminate and the two sub laminates separated by the pre-crack at mid-plane. These specimens have different ply orientations, but their elastic properties are exactly the same. Hence differences in mode I delamination behavior are only due to local fiber orientation effects. Experimental results show that the measured toughness at the crack initiation decreases with both adjacent and sub-adjacent ply angles. During the crack propagation, the plateau value of the R-curve increases with the ply angle of adjacent plies.